2019
DOI: 10.2174/0929867326666181213093152
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide in Life and Death of Neutrophils

Abstract: Background: Nitric Oxide (NO) is a key signalling molecule that has an important role in inflammation. It can be secreted by endothelial cells, neutrophils, and other cells, and once in circulation, NO plays important roles in regulating various neutrophil cellular activities and fate. Objective: To describe neutrophil cellular responses influenced by NO and its concomitant compound peroxynitrite and signalling mechanisms for neutrophil apoptosis. Methods: Literature was reviewed to assess the effects of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Co-expression analysis of the expression levels of immune cells obtained in this study showed that the correlation between T cells regulatory (Tregs) [10][11][12][13]and Neutrophils [14][15][16][17] was the strongest, with a coe cient of 0.78, and the two cells with the weakest correlation were Macrophages [18][19] and T cells follicular helper [20][21], the correlation coe cient is -0.59 (Figure 3).…”
Section: Co-expression Analysis Between Immune Cellsmentioning
confidence: 77%
“…Co-expression analysis of the expression levels of immune cells obtained in this study showed that the correlation between T cells regulatory (Tregs) [10][11][12][13]and Neutrophils [14][15][16][17] was the strongest, with a coe cient of 0.78, and the two cells with the weakest correlation were Macrophages [18][19] and T cells follicular helper [20][21], the correlation coe cient is -0.59 (Figure 3).…”
Section: Co-expression Analysis Between Immune Cellsmentioning
confidence: 77%
“…Co-expression analysis of the expression levels of immune cells obtained in this study showed that the correlation between T cells regulatory (Tregs) [10][11][12][13]and Neutrophils [14][15][16][17] was the strongest, with a coe cient of 0.78, and the two cells with the weakest correlation were Macrophages [18][19] and T cells follicular helper [20][21], the correlation coe cient is -0.59 (Figure 3). After obtaining the matrix of immune cells, we wondered whether these immune cells could distinguish between the normal group and the tumor group.…”
Section: Co-expression Analysis Between Immune Cellsmentioning
confidence: 77%
“…Nitric oxide (NO), also known as endothelium-derived relaxing factor [ 73 ], is derived from the oxidation of L-arginine amino acid by nitric oxide synthase [ 74 ]. It facilitates vascular homeostasis by maintaining vascular integrity and inhibiting platelet aggregation and neutrophil adhesion [ 75 , 76 ]. Nitric oxide also prevents the proliferation of artery smooth muscle cells in defense against atherosclerosis and neointima hyperplasia formation [ 77 , 78 ].…”
Section: Hydroxytyrosol In Oxidative Stress-induced Endothelial Dysfu...mentioning
confidence: 99%